2020
DOI: 10.4236/ojneph.2020.103019
|View full text |Cite
|
Sign up to set email alerts
|

Study the Role of Lung Ultrasound in Assessment of Subclinical Fluid Overload in Maintenance Hemodialysis Patients with Intra-Dialytic Hypertension

Abstract: Objectives: To elucidate the role of lung ultrasound in assessment of subclinical fluid overload in hemodialysis (HD) patients. Background: Volume overload has a significant role in HD patients with difficult blood pressure control. The clinical evaluation of fluid status is challenging and has poor diagnostic accuracy. Extravascular lung water (ELW) represents an important element of body fluid volume. Lung ultrasound (LUS) is increasingly used for ELW assessment through the analysis of B-lines artifacts. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…This is similar to findings by Siriopol et al [9], Khamis et al [20] and Mallamaci et al [22]. Whereas Vitturi et al [24] obtained a relatively low number of B-lines, and they described a high correlation between the decrease in the number of B-lines and weight loss after dialysis.…”
Section: Analysis Of the Correlation Of Measured Parameters And B-linessupporting
confidence: 89%
See 2 more Smart Citations
“…This is similar to findings by Siriopol et al [9], Khamis et al [20] and Mallamaci et al [22]. Whereas Vitturi et al [24] obtained a relatively low number of B-lines, and they described a high correlation between the decrease in the number of B-lines and weight loss after dialysis.…”
Section: Analysis Of the Correlation Of Measured Parameters And B-linessupporting
confidence: 89%
“…B-lines are associated with the accumulation of water during the interdialytic period and reflect the variation in the level of extravascular lung water which occurs during dialysis [32]. In their study, Khamis et al also showed a significant decrease of number of B-lines post-dialysis, especially for the group of patient with interdialytic hypertension (from 10 to 4 B-lines) [20]. Noble et al [33] and Mallamaci et al [22] proved that the number of B-lines rapidly and in a reliable manner reflects the extracellular fluid variation, with an average duration of 4 minutes for the change on the screen [22].…”
Section: Analysis Of the Variation In Clinical And Sonographical Sign...mentioning
confidence: 89%
See 1 more Smart Citation
“…According to a research report, sleep disturbance is one of the six most troublesome symptoms of hemodialysis patients, and the prevalence rate is as high as 86%. This seriously affects the quality of life of patients and increases the risk of death in dialysis patients and affects disease prognosis [ 15 ].…”
Section: The Relationship Between Hemodialysis and Sleep Disorders In...mentioning
confidence: 99%